Energy constraints and future spatial patterns of American cities - Costa, Frank J.; Dutt, Ashok K. (The Greek Review of Social Research, 1976)
During the modern industrial era there have developed several significant changes in urban land use and transportation patterns. These changes are largely tied to the use of energy in combination with new technology. This paper seeks to examine how urban land use and transportation patterns have responded to continually increasing per capita energy consumption levels. New energy consumption levels associated with expected enervi shortages are also examined. It is theorized that the spatially-expanding urban complexes of today will begin to solidify and become more densely utilized with respect to both land use and population settlement. This new urban spatial pattern will highlight the need for sound and comprehensive regional land-use planning. A model of planning organization in such a context is proposed which seeks to achieve regional development objectives within the context of declining per capita energy consumption.